Feminisme dalam Fenomena Childfree : Analisis Wacana Kritis Sara Mills pada Buku “Childfree And Happy” - Mardika, Mifta Rizki; Ashaf, Abdul Firman; Utaridah, Nanda (Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis research discusses social phenomena childfree in mass media (books) which are one of the agendas of the feminism movement. Victoria Tunggono is the first Indonesian writer who voice childfree loudly through her book entitled